2020
DOI: 10.2147/opth.s285443
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Factors for Visual Outcomes Following the First Episode of NMOSD-Related Optic Neuritis in Affected Eyes</p>

Abstract: Objective: We aim to identify prognostic factors for visual outcomes following a first episode of neuromyelitis optica spectrum disorder-related optic neuritis (NMOSD-ON) in affected eyes. Materials and Methods: This was a single-center, retrospective study. The study included 50 individuals who were diagnosed with NMOSD-ON (63 affected eyes) in a tertiary institution over a 12-year period. Data regarding any second, or higher, episodes of NMOSD-ON in each eye were not taken into consideration. Medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“… 2–4 Moreover, our previously published article, which studied prognostic factors for visual outcomes following the first episode of ON in each affected eye in overall age group of NMOSD-ON patients, showed that a median age at NMOSD-ON onset was 36 years (range 4–84 years). 18 Notably, unlike our previously published article, patients with age < 18 years at NMOSD-ON onset were excluded in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2–4 Moreover, our previously published article, which studied prognostic factors for visual outcomes following the first episode of ON in each affected eye in overall age group of NMOSD-ON patients, showed that a median age at NMOSD-ON onset was 36 years (range 4–84 years). 18 Notably, unlike our previously published article, patients with age < 18 years at NMOSD-ON onset were excluded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Moreover, our previously published article, which studied prognostic factors for visual outcomes following the first episode of ON in each affected eye in overall age group of NMOSD-ON patients, showed that a median age at NMOSD-ON onset was 36 years (range 4-84 years). 18 Notably, unlike our previously published article, patients with age < 18 years at NMOSD-ON onset were excluded in this study. Small proportions of patients in the LO-NMOSD-ON (20%) and EO-NMOSD-ON groups (31.8%) experienced non-ON demyelinating events prior to or concurrent with ON onset; notably, myelitis was the most common event.…”
Section: Demographic Datamentioning
confidence: 99%
“…Additionally, MRI is crucial to exclude differential diagnoses as well as for the evaluation of inflammatory lesions during follow-up [17]. While brain MRI lesions in both NMOSD and MOGAD have been described [9][10][11][12][13][14][15][16][17][18], only a few previous studies have evaluated the radiological features of NMOSD-ON versus MOGAD-ON, focusing on optic chiasm involvement [19][20][21][22][23].…”
Section: Although Conventional Brain Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…By contrast, MOGAD-ON is associated with the optic nerve sheath or extends into the orbital fat with gadoliniumenhancing lesions more than half of the length of the optic nerve in 80% of patients [19,24]. Optic chiasm lesions on MRI have been reported in up to 64% of NMOSD-ON patients seropositive for AQP4-ab, while in MOGAD-ON they were reported in up to 16% [19][20][21][22][23]. Thus, frequency rates vary widely between distinct populations worldwide.…”
Section: Although Conventional Brain Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation